Internationalization vs. family ownership and management: The case of Portuguese wine firms - Pacheco, Luís Miguel (2017)
Purpose: The objective of this paper is to empirically examine the relationship between the firms’ ownership and control structure and their export performance. The literature is traditionally focused on the relation between firms’ performance and internationalization, with the relation between ownership and control structure with internationalization being much less studied, particularly in the context of family firms. Design/methodology/approach: We focus our study on the Portuguese wine firms due to their increasing importance in the Portuguese economy and in the promotion of the country’s exports and image abroad. It is used a balanced panel data sample of 82 firms for the period from 2011 to 2015 and applied a random effects model and a Tobit specification. Findings: The degree of family involvement shows a negative and significant relationship with internationalization, meaning that family firms that intend to internationalize should be open to receive external managers with international experience and increase their internal competencies in order to enhance internationalization. Originality/value: This paper extends the literature since assesses, at the light of the agency theory, the presence of differences in the internationalization degree and export intensity between family firms that are managed and controlled by the owners and family firms that are managed by non-family members, with an application to a less studied sector and country.